Drama, Performance, and Polity in Pre-Cromwellian Ireland - Fletcher, Alan J. (Book collections on Project MUSE., 2000)
"The Irish contribution to world theatre is famous, but today awareness of Irish theatrical activity is chiefly confined to the modern period. This book corrects that imbalance with an unparalleled study of the early history of drama and performance in Ireland, from the seventh century through the sixteenth and seventeenth centuries, and ending on the eve of the arrival of Oliver Cromwell. The work of professional entertainers is discussed, as is that of amateurs, in theatricals sponsored by churches, guilds, civic authorities, and aristocratic patrons."--Jacket.